Giant cells in pigmented villo nodular synovitis express an osteoclast phenotype. Issue 7 (July 1997) - Neale, S D; Kristelly, R; Gundle, R; Quinn, J M; Athanasou, N A
Abstract : AIM: To determine the cytochemical and functional phenotype of multinucleated giant cells in pigmented villo nodular synovitis (PVNS). METHODS: Giant cells isolated from a patient with PVNS of the knee were assessed for a number of markers used to distinguish osteoclasts from macrophages/ macrophage polykaryons: evidence of tartrate resistant acid phosphatase (TRAP) activity; expression of CD11b, CD14, CD51, and calcitonin receptors; and the ability of the giant cells to carry out lacunar resorption. RESULTS: Isolated giant cells expressed an osteoclast antigenic phenotype (positive for CD51, negative for CD11b and CD14) and were TRAP and calcitonin receptor positive. They also showed functional evidence of osteoclast differentiation, producing numerous lacunar bone resorption pits on bone slices in short term culture. CONCLUSIONS: The giant cells in this case of PVNS express all the phenotypical features of osteoclasts including the ability to carry out lacunar resorption. This may account for the bone destruction associated with this aggressive synovial lesion.